CAREC energy strategy 2030 common borders common solutions common energy future. (Regional cooperation strategy and programs., 2019)
It discusses how the 11 CAREC countries can improve regional energy connectivity and implement priority reforms to scale up investments and promote green energy. It also proposes measures to empower women in the energy sector and build knowledge through new institutional partnerships.